A 12‐week, randomized, double‐blind, placebo‐controlled, four‐arm dose‐finding phase 2 study evaluating bexagliflozin as monotherapy for adults with type 2 diabetes. Issue 4 (11th December 2019) - Halvorsen, Yuan‐Di; Walford, Geoffrey; Thurber, Tara; Russell, Heidy; Massaro, Monica; Freeman, Mason W.
Abstract: Aim: To compare the safety and efficacy of bexagliflozin administered as monotherapy at three dosage strengths over a 12‐week period to patients with type 2 diabetes who were either naïve to pharmacotherapy or were previously prescribed one oral hypoglycaemic agent and underwent a 6‐week period of medication abstinence. Methods: Adults with type 2 diabetes (n = 292) having an HbA1c of between 7.0% and 8.5% were randomized to receive one of three dosage strengths of bexagliflozin (5, 10 or 20 mg) or placebo. The primary endpoint was the change from baseline to week 12 in the %HbA1c. Secondary endpoints included the changes from baseline in fasting plasma glucose (FPG), systolic blood pressure and diastolic blood pressure, body mass and fraction of patients achieving an HbA1c of <7%. Results: The mixed model repeated measure estimates of the placebo‐adjusted change in %HbA1c from baseline to week 12 for the 5, 10 and 20 mg groups were −0.55% (95% CI: −0.76%, −0.34%, P < 0.0001), −0.68% (95% CI: −0.89%, −0.47%, P < 0.0001) and −0.80% (95% CI: −1.01%, −0.59%, P < 0.0001), respectively. Significant and dose‐dependent placebo‐adjusted mean reductions from baseline to week 12 in FPG and body mass were observed. The fraction of subjects achieving an HbA1c of <7% was significantly greater in the 20 mg bexagliflozin group. The incidence of adverse events was similar for participants in all active arms (42.3%) compared with the rate measured in those receiving placebo (40.3%). Conclusions: Bexagliflozin confers substantial and dose‐dependent benefits on subjects with type 2 diabetes and has an acceptable safety profile. Further evaluation of bexagliflozin for the control of type 2 diabetes in adults is warranted.